Análise da interação profissional-paciente no atendimento odontopediátrico como requisito para a capacitação do dentista para o trabalho com pacientes especiais - Rolim, Gustavo Sattolo (2006)
The dental treatment and all its components (behaviors and the clinical environment) frequently acquire aversive functions. The objective of this study was to describe strategies used by the dentist and its effects on children s escape or avoidance behaviors during the dental treatment. Participants were a dentist and six children with previous history of traumatic dental treatment. Two studies were carried out. In first study the procedure consisted of eight sessions separated by two Experimental Conditions. In the First Condition, treatment should be conducted at the first 4 sessions with an explicit requirement of not using children s Physical Restraint. This requirement was suspended for the Second Condition. In the other study, two dental treatments were carried out without any special requirement, separated by an interval of two years. For both studies, all the sessions were recorded in VHS and behavioral events sequentially analyzed. Children and professional s behaviors were recorded in a formal protocol. The treatments were analyzed session by session and in each dental routine. Records were made by independent observers. Results showed that children with a history of non-cooperative behaviors when exposed to the same type of situation presented a reduction in the frequency of non-cooperative behaviors, what can be supposed to be a result of an extinction process. Extinction also occurred concerning dentist´s interactive responses. Dentist used Physical Restraint to manage dental treatment. Participant 1 showed cooperative behaviors during almost all treatment sessions. When the dentist used Physical Restraint, this child emitted escape responses. For Participant 2, Physical Restraint worked as punition, because it suppressed non-cooperative behaviors. Considering the treatment of Participants 3, 4, 5 and 6 data reveals the possibility of an extinction process of non-cooperative behaviors. Results suggest that the dentist and child learn with each other during dental treatment, and this situation is important not only for the dental health, but also for the promotion and development of coping repertoires with situations that involve aversive events.